Euphoria : a novel - King, Lily (Atlantic Monthly Press, 2014)
"English anthropologist Andrew Bankson has been alone in the field for several years, studying the Kiona river tribe in the Territory of New Guinea. Haunted by the memory of his brothers' deaths and increasingly frustrated and isolated by his research, Bankson is on the verge of suicide when a chance encounter with colleagues, the controversial Nell Stone and her wry and mercurial Australian husband, Fen, pulls him back from the brink. Nell and Fen have just fled the bloodthirsty Mumbanyo and, in spite of Nell's poor health, are hungry for a new discovery. When Bankson finds them a new tribe nearby, the artistic, female-dominated Tam, he ignites an intellectual and romantic firestorm between the three of them that burns out of anyone's control" --